Roles of secretory leukocyte protease inhibitor amniotic membrane in oral wound healing - Elly Munadziroh (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
Secretory Leukocyte Protease Inhibitor (SLPI) is serine protease inhibitor. Secretory Leukocyte Protease Inhibitor is a protein found in secretions such as whole saliva, seminal fluid, cervical mucus, synovial fluid, breast milk, tears, and cerebral spinal fluid, as in secretions from the nose and bronchi, amniotic fluid and amniotic membrane etc. These findings demonstrate that SLPI function as a potent anti protease, anti inflammatory, bactericidal, antifungal, tissue repair, extra cellular synthesis. Impaired healing states are characterized by excessive proteolysis and often bacterial infection, leading to the hypothesis that SLPI may have a role in the process. The objectives of this article are to investigate the role of SLPI in oral inflammation and how it contributes to tissue repair in oral mucosa. The oral wound healing responses are impaired in the SLPI sufficient mice and matrix synthesis and collagen deposition are delayed. This study indicated that SLPI is a povital factor necessary for optimal wound healing.